IR 레이저 기반 연기감지기를 위한 고정밀 자동초점 정합장치에 관한 연구 - 김관형; 신동석; 오암석; Kim, Gwan-Hyung; Shin, Dong-Suk; Oh, Am-Suk (한국정보통신학회논문지, 2014)
Smoke detector is commonly used to reduce fire detection time. However, technical problems regarding its inaccuracy of laser beam-receiving point on the surface of the sensor associated with incoming interference are identified when the laser transmitter and receiver are installed at a distance of about 100m. In this paper, we propose the auto focus alignment algorithm with high precision to adjust tilting angle of lasers caused by environmental interference so that solve existing issues using multi-level worm gear set. 화재감지 시간을 단축하기 위해서 연기감지기가 활용되는 추세이며, 발신기와 수신기가 100m이상 이격되어 설치되는 구조의 연기감지기는 외부환경의 영향으로 인한 발신기의 각도변화에 따라 수광부 레이저 포인트 위치가 매우 민감하게 변화한다. 본 논문에서는 레이저 발신기와 수신기 간의 원거리 설치에 따른 레이저 초점 설정의 어려움을 해결하고 외부 환경에 따른 초점 정합의 문제를 해결하기 위해서 다중 웜기어를 활용한 고정밀 제어장치와 레이저 광선의 틀어진 각도를 조정 할 수 있는 자동초점 정합 알고리즘을 제시한다.